A Kabbalah and Jewish Mysticism Reader - Horwitz, Daniel M. (Book collections on Project MUSE., 2016)
An annotated anthology of Jewish mystical works, concepts, and experiences, A Kabbalah and Jewish Mysticism Reader explores issues relating to what has compelled Jews to seek a more intimate relationship with God. It does this by providing readings from the most important mystical texts, accompanied by Daniel M. Horwitz's insightful introductions and commentary. It is carefully designed to make the basic concepts and teachings of Jewish mysticism accessible to a wide audience and to ground these ideas within the broader Jewish tradition. Horwitz's introduction describes five major types of Jewish mysticism and includes a brief chronology of their development, with a timeline. He begins with biblical prophecy and proceeds through the early mystical movements up through current beliefs. Chapters on key subjects characterize mystical expression through the ages, such as Creation and deveikut ("cleaving to God"); the role of Torah; the erotic; inclinations toward good and evil; magic; prayer and ritual; and more. Later chapters deal with Hasidism, the great mystical revival, and twentieth-century mystics, including Abraham Isaac Kook, Kalonymous Kalman Shapira, and Abraham Joshua Heschel. A final chapter addresses today's controversies concerning mysticism's place within Judaism and its potential for enriching the Jewish religion. -- Amazon.com